Forest-Smart Mining : Identifying Factors Associated with the Impacts of Large-Scale Mining on Forests - Maddox, Thomas (World Bank, Washington, DC, 2019)
Minerals play a vital role in society, both in everyday life and in technologies required for a greener economic future. While circular economic approaches are developing fast, continued rising demand and the limitations of recycling mean mining for new raw materials is set to remain an important part of mineral production for the foreseeable future. As an industry, mining plays an important role in more than 80 countries worldwide and, when managed well, contributes to many of the global development goals. However, when managed poorly, the sector can lead to various negative social, environmental, and economic impacts potentially occurring across the mining life cycle. Change in the mining sector tends to be slow, with activity largely driven by long-term commodity price cycles and projects being conducted at increasingly larger scales. But when projects do occur, they can play a key role in the future development of an area. This report focuses on large-scale mining (LSM), with the stated outcome being the identification of good and bad practices and or enabling conditions related to promoting forest-smart LSM based on a series of case studies.